Forming Students' Morals Through the Habit of Reading Asmaul Husna Using the Hanifida Method in Class VII MTs Darun Nahwi Singajaya Indramayu - Ibnu Rusydi; Didik Himmawan; Fiqri Nurhasanah (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Emulating the nature of Allah contained in Asmaul Husna does not mean emulating God, but trying to form a person who has noble character. Asmaul Husna is a series of beautiful names, holding grace and enjoyment for every human being who desires the pleasure of Allah SWT. The Hanifida method is a practical method of fast memorization, namely using a constructivist model, where knowledge is built little by little through visualization, imagination, stories full of action and with emotions that are created by yourself according to real life contexts, and this method functions the right brain and left brain in a balanced way. Apart from increasing faith and getting rewards, the habit of reading Asmaul Husna using the Hanifida method is one way to know, understand, and memorize the Names of Allah SWT. Based on the description above, the researcher intends to conduct research with the aim of finding out the implementation of the formation of students' morals through the habit of reading Asmaul Husna using the Hanifida method in class VII MTs Darun Nahwi and the impact of forming students' morals through the habit of reading Asmaul Husna using the Hanifida method in class VII MTs Darun Nahwi. The conclusion of this research is the positive impact of the habit of reading Asmaul Husna using the Hanifida method in class VII MTs Darun Nahwi, namely that students can apply it in daily life such as dhikr after prayer.